DIPG-55. TARGETING SENESCENT CELLS WITH ABT-263 ENHANCES CELL DEATH INDUCED BY BMI1 INHIBITION AND IONIZING RADIATION IN DIPG. Issue 2 (22nd June 2018) - Balakrishnan, Ilango; Madhavan, Krishna; Pierce, Angela; Dahl, Nathan; Lemma, Rakeb; Fosmire, Susan; Wang, Dong; Prince, Eric; Alimova, Irina; Hashizume, Rintaro; Huellman, Esther; Hawkins, Cynthia; et al.
Abstract: Ionizing Radiation (IR) is a key treatment modality for DIPG, but it provides only temporary relief as the tumor cells develop resistance to radiation. Recently, we and others have shown that inhibition of BMI1 either alone or in combination with radiation attenuates DIPG cell proliferation in vitro. While we are demonstrating the in vivo efficacy of pharmacological inhibition of BMI1 and understanding the mechanism of anti-tumor effect of BMI1 inhibition in DIPG, the existence of treatment-resistant cells remains a major obstacle for a prolonged cure. Both IR and genetic or pharmacological inhibition of BMI1 induces cellular senescence as a mechanism to suppress tumor cell proliferation, implying that senescence can be considered as tumor suppressor. Paradoxically, recent studies have shown that accelerated senescence can mediate tumor recurrence due to the development of pro-oncogenic environment. In line with this, we are investigating whether clearance of treatment-induced senescent cells enhances treatment outcomes. DIPG cells exposed to different doses of radiation followed by treatment with ABT-263 (Navitoclax), a drug which selectively clears the senescent cells, resulted in increased radiosensitization. Treatment of pre-radiated DIPG cells with ABT-263 decreased the activity of senescence-associated beta-galactosidase and anti-apoptotic protein expression. Similarly, chemical inhibition of BMI1 in combination with ABT-263 showed synergistic killing of DIPG cells. The synergy was most pronounced in DIPG cells harboring wildtype p53. Our study highlights the importance of eliminating treatment-induced senescent cells while inhibiting proliferation of DIPG tumors, a combination which can immensely improve therapeutic efficacy in DIPG patients.